(untitled) (Ibrahim Cardiac Medical Journal, 2018)
Background & objective: Road traffic accident (RTA), now a days, has become a common event worldwide. As face is the most exposed part of the body, is most at risk of sustaining trauma in RTA. However, there is paucity of information regarding the relationship between head injuries and facial trauma. A number of reviews have looked at brain injuries in patients with facial fractures. But these reviews failed to differentiate between major and minor brain injuries. Moreover, most studies were retrospective and based upon large trauma registries, which tend to preselect patients with multiple trauma and capture only major brain injuries. The incidence of minor brain injuries and concussion in this population is thus overlooked. This study was aimed to find the proportion of major and minor brain injuries in patients with facial bone fracture. Materials & Methods: This cross-sectional study was carried out in patients with facial bone fractures who attended at outpatient clinic, hospital ward of the Department of Oral and Maxillofacial Surgery, Dhaka Dental College Hospital, Dhaka, Neurosurgery Department, Emergency Department of Intensive Care Unit of Dhaka Medical College Hospital, Dhaka over a period of 2 years from January 2012 to December 2013. Only the patients of first encounters were included in the study. Patients referred from other centers with facial bone fracture were excluded. A total of 150 such patients were enrolled in the study. To assess and communicate the extent of an unconscious patient’s injury rapidly Glasgow Coma Scale (GCS) was used. The outcome variable was brain injury (major and minor). Result: Majority (80%) of the patients was male with mean age of the patients being 25 years (range: from 4 – 80 years). The most common mechanism of injury in the present study was road-traffic accident (60%), followed by assault (20%), fall from height (12%), crash (6%) and blast trauma (2%). Nearly half (46%) of the patients had multiple facial bone fractures. Over 10% of the patients received Zygomatico-maxillary complex fracture. Mandible fracture and frontal bone fracture each accounted for 7.3%. Nasal bone fracture was 6.7%, isolated maxilla fracture was 5.3%, Le Fort I fracture was 4.7% and orbital floor fracture was 4.0%. The Glasgow coma score 12 or below 12 was found in 52% cases and loss of consciousness and perievent amenesia were observed in 54% and 56% cases respectively. The major and minor brain injuries were found in 52% and 32% cases respectively together comprising an occurrence of 84% in facial bone fractures. Male patients, receiving trauma through RTA and multiple facial bones fractures were significantly associated with brain injury (p = 0.019, p < 0.001, p = 0.001 respectively). However, mandible and nasal bone fractures were less prone to be associated with brain injury in (p = 0.001 and p < 0.001 respectively). Conclusion: The study concluded that majority of the patients with facial bone fractures have had concomitant brain injuries. Male patients, receiving trauma through RTA and multiple fractures of the facial bones are more prone to be associated with brain injury than females, receiving injury through mechanisms other than RTA and isolated facial bone fractures. Ibrahim Card Med J 2016; 6 (1&2): 33-40